THE PARASITISM OF Eretmocerus mundus MERCET (HYMENOPTERA; APHELINIDAE) ON Bemisia tabaci GENNADIUS (HOMOPTERA; ALEYRODIDAE) and ITS MASS REARING ON SEVERAL ALTERNATIVE HOSTS - Sudarjat -; Natasasmita, S -; Hadiani, R.U - (Bionatura, 2012)
Sweet potato whitefly Bemisiatabaci Gennadius is one of major pests of vegetables. One of techniques to control this pest is the use of parasitic wasp Eretmocerus mundus Mercet. This research was aimed to find out the effect of host density on level of parasitization and alternative host for mass rearing of E. mundus. This research was carried out at green house of the Departement of Plant Pests and Diseases, Faculty of Agriculture, Universitas Padjadjaran. In parasitization test, the experiment was arranged in a randomized block design consisting of six treatments (50, 100, 150, 200, 250, and 300 nymphs ofB. tabaci) and four replications. In alternative host test, five treatments (B. tabaci, Trialeurodessp., Aleurodicus sp., Aleurocanthus sp., and Aphis gossypii) were used. The result showed that host density affected on the parasitization level. The highest parasitization occurred at host density of 200 nymphs,that was 29.25%. Trialeurodes sp. and Aleurodicus sp. can be parasitized by E. mundus with levels of parasitization were 19.6% and 2.6%, respectively. There was no significant different between the parasitization on Trialeurodessp. (19.6%) and B. tabaci (24%). However, the performances of the parasitoid (parasitization level, adult emergence, and host feeding behaviour) reared on B. tabaci was better than those reared on Trialeurodes sp.Key word: Eretmocerus mundus, mass rearing, alternative host